Infective Endocarditis Associated with Multisystem Inflammatory Syndrome in Children (MIS-C): Two Case Studies - Nazrin, Tahera; Hassan, M Quamrul (Pulse, 2023)
Infective endocarditis (IE) is the infection of endocardial surface of the heart. IE is the rare disease with significant complications which require early diagnosis and proper treatment for reducing morbidity and mortality.IE with vegetation on pulmonary valve, leaflets are uncommon. However, we have diagnosed one case with infective endocarditis associated with Multisystem Inflammatory Syndrome in Children (MIS-C) which is related with COVID-19. MIS-C is commonly associated with coronary artery aneurysm (CAA), myocarditis and heart failure. Our patient had IE and was subsequently affected with MIS-C due to COVID. The child had vegetation on pulmonary valve with flail pulmonary valve-leaflet with grade II pulmonary regurgitation and MIS-C related CAA. The second child was previously diagnosed as infective endocarditis and was treated in other hospital for intravenous antibiotic for four weeks. However, in our hospital he was diagnosed clinically, by laboratory investigations and by echocardiography as MIS-C with large vegetation, which was surgically removed, and biopsy revealed mycobacterium tuberculosis as causative organism. Pulse Volume 12-14 2020-2022 p.26-31